Diversitas Capung (Odonata) di Sekitar Kampus Universitas Udayana, Bukit Jimbaran, Bali - Theresa, Fransiska Yulianita; Suartini, Ni Made; Ginantra, I Ketut (Bumi Lestari Journal of Environment, 2024)
Insects are the Arthropod phylum that has the highest diversity. One of the most common insects in Indonesia is the dragonfly (Odonata), which consists of the Anisoptera suborder and the Zygoptera suborder. This study aims to determine the dragonflies species that are found around the Udayana University Campus, Bukit Jimbaran, Bali. Sampling of dragonfly was carried out by sweeping technique using insect nets in the morning (08.00-10.00 WITA) and in the afternoon (15.00-17.00 WITA). Sampling was carried out at three different locations, including location I: Biology-Rectorate, Location 2: Dean of FMIPA-FTP, Location 3: Udayana Forest-Dam. Each location was repeated three times in the morning and evening. Species identification and species number calculations were carried out for analysis using the Shannon-Wiener diversity index (H'), evenness index (E) and Simpons dominance index (D). There are 8 species of dragonflies found and belong to two suborders. A total of seven species found belong to the Anisoptera Suborder and one species belongs to the Zygoptera Suborder. The overall diversity of dragonflies with a value of 1.83 is included in the moderate category, evenness is included in the even category with a value of 0.94 and a dominance value of 15% which indicates that no species dominates. Keywords: Diversity, Dragonflies, Udayana University